Possible roles for environmental Life Cycle Assessment in building specifications - Grant, Tim; Hes, Dominique (Acta Structilia, 2009)
Life Cycle Assessment (LCA) is a systematic methodology for evaluating the environmental impacts of different product systems. It is a useful tool for comparing different alternative products or systems (including buildings. However, complexities of the built environment and limitations in current LCA data and methodology make implementation of LCA into decision making for building design and specification, very difficult. Streamlined LCA techniques and life cycle thinking are currently the easiest ways to introduce LCA to the building sector. However, in the future, with new developments in LCA. more rigorous tools should become available.